Bildsprache und Sprachbilder in der Prosa und Prosatheorie Jan Kjaerstads - Brynhildsvoll, Knut (Folia Scandinavica Posnaniensia, 2007)
In all his novels Jan Kjærstad in a very significant manner makes use of pictorial descriptions. The objects, which he describes, oscillate between famous pictures of artists like Vermeer, Picasso, Gauguin, van Gogh and imaginary ones, which are the products of the author’s own phantasy. Together the descriptions of real and fictional objets d’art shape a network of interpictorial patterns, which are typical for Kjaerstad’s way of writing. These interfigural traces seem to me to be very important parts of the textual conception of his novels and they obviously have a metaphoric function. In my contribution I focus on some aspects of this metaphoric structure by means of pictorial description and show some semantic implications of the interpictorial relations and of the basic communications between verbal and graphic signs, which in the novels of Kjærstad can be traced back to a common point of departure, in which there is no difference between written and pictorial expression.